(untitled) (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the relationship between the quality of nursing services and the level of satisfaction of inpatients in a hospital. The method used is a descriptive approach with descriptive statistical analysis. The results showed that all respondents gave the same assessment of service quality (score 36) and patient satisfaction (score 50) with a standard deviation of 0, indicating a homogeneous perception. This indicates that the quality of nursing services and patient satisfaction are at a high and uniform level. However, the uniformity of the data indicates the need for a more sensitive instrument to detect variations in respondents’ perceptions. The conclusion is that the quality of nursing services has a positive effect on patient satisfaction. Keywords: Patient satisfaction, Quality of nursing services, Health services, Hospitals